Cord blood–derived T cells allow the generation of a more naïve tumor‐reactive cytotoxic T‐cell phenotype. Issue 1 (11th October 2017) - Kwoczek, Julian; Riese, Sebastian B.; Tischer, Sabine; Bak, Szilvia; Lahrberg, Julia; Oelke, Mathias; Maul, Holger; Blasczyk, Rainer; Sauer, Martin; Eiz‐Vesper, Britta
Abstract : BACKGROUND: Transplantation of hematopoietic stem cells (HSCs) from peripheral blood (PB) or cord blood (CB) is well established. HSCs from CB are associated with a lower risk of graft‐versus‐host disease (GVHD), but antigen‐independent expanded CB‐ and PB‐derived T cells can induce GVHD in allo‐HSC recipients. CB‐derived cells might be more suitable for adoptive immunotherapy as they have unique T‐cell characteristics. Here, we describe functional differences between CB and PB T cells stimulated with different cytokine combinations involved in central T‐cell activation. STUDY DESIGN AND METHODS: Isolated CD8+ T cells from CB and PB were stimulated antigen independently with anti‐CD3/CD28 stimulator beads or in an antigen‐dependent manner with artificial antigen‐presenting cells loaded with the HLA‐A*02:01‐restricted peptide of tumor‐associated melanoma antigen recognized by T cells 1 (MART1). CB and PB T cells cultured in the presence of interleukin (IL)‐7, IL‐15, IL‐12, and IL‐21 were characterized for T‐cell phenotype and specificity, that is, by CD107a, interferon‐γ, tumor necrosis factor‐α, and IL‐2 expression. RESULTS: After antigen‐independent stimulation, activated CD8+ CB T cells exhibited stronger proliferation and function than those from PB. After antigenic stimulation, MART1‐reactive CB T cells were naïve (CD45RA+CCR7+), cytotoxic, and highly variable in expressing homing marker CD62L. Addition of IL‐21 resulted in increased T‐cell proliferation, whereas supplementation with IL‐12 decreased IL‐21–induced expansion, but increased the functionality and cytotoxicity of CB and PB T cells. CONCLUSION: MART1‐reactive CB T cells with a more naïve phenotype and improved properties for homing can be generated. The results contribute to better understanding the effects on GVHD and graft versus tumor.